Critical Chain Project Management and Buffer Planning: Study Case at Security Accommodation Vessel Construction - Bella Puji Darma Samodra; Agoes Santoso; Ede Mehta Wardhana (International Journal of Marine Engineering Innovation and Research, 2025)
Shipbuilding projects frequently encounter delays and cost overruns as a result of unpredictability in the construction process. This paper aims to explore the potential of Critical Chain Project Management (CCPM) and buffer planning to enhance scheduling in complex shipbuilding project. The research approach involves a case study of a Security Accommodation Vessel (SAV) construction project, complemented by expert interviews which were conducted to assess the risks and uncertainties affecting activity durations. The buffer sizes were then calculated using the Root Square Error Method (RSEM). Qualitative data was gathered through interviews with the expert to identify and assess potential risks and uncertainties impacting activity durations. This qualitative insight informed the application of the RSEM to determine appropriate buffer sizes. The planned project duration was reduced from 790 days to 678 days, representing a 14,5% improvement. The study focuses on the planning phase of CCPM and demonstrates the potential of combining CCPM, buffer planning, and expert input to create more reliable schedules for complex shipbuilding projects like SAV construction.